Gynecologic Cancer InterGroup (GCIG) Consensus Review for Endometrial Stromal Sarcoma. (1st November 2014) - Amant, Frédéric; Floquet, Anne; Friedlander, Michael; Kristensen, Gunnar; Mahner, Sven; Nam, Eun Ji; Powell, Matthew A.; Ray-Coquard, Isabelle; Siddiqui, Nadeem; Sykes, Peter; Westermann, Anneke M.; Seddon, Beatrice
Abstract : Abstract: Endometrial stromal sarcoma (ESS) accounts for approximately 20% of all uterine sarcomas and presents, at a mean age, around 50 years of age. Half of the patients are premenopausal. ESS often manifests as an endometrial polyp and 60% of cases present with FIGO stage I disease. The natural history is one of slow growing indolent disease. Typical microscopic findings include a uniform population of endometrial stromal-type cells invading the myometrium and myometrial vessels. Imaging studies cannot reliably diagnose ESS preoperatively, so surgical resection for a presumed fibroid is a common scenario. Hysterectomy is the cornerstone of treatment for localized ESS, but morcellation should be avoided. Systematic lymphadenectomy in ESS does not improve the outcome. Leaving the ovaries in situ does not worsen survival and this is of importance especially for young women. The data support the current practice to administer adjuvant hormonal treatment, although several questions remain, such as optimal doses, regimens (progestins or aromatase inhibitors) and duration of therapy. Repeat surgery for recurrent disease that is indolent and hormone sensitive appears to be an acceptable approach. Systemic treatment for recurrent disease is mainly hormonal.